Taxonomic revision of the Neotropical genus Arthropeina Lindner, 1949 (Diptera: Xylomyidae) - Fachin, Diego Aguilar; de Souza Amorim, Dalton (Zootaxa, 2014)
Five new species are herein described for the Neotropical genus Arthropeina previously known only from the type–species, A. fulva Lindner: A. colombiana, sp. nov., A. diadelothorax, sp. nov., A. lindneri, sp. nov., A. melanochroma, sp. nov. and A. pseudofulva, sp. nov. The new species are described and habitus, antenna, palpus, thorax, wing, and male and female genitalia, including genital fork and spermathecae, are illustrated. A key to the species of the genus is provided. The diagnosis of Arthropeina is emended to include these new species. Additionally, the genus is recorded for the first time for Guyana, Colombia, Ecuador, Peru and Bolivia.